Evaluation of Hotel Employee Readiness Preparation for the First COVID - 19 Pandemic prevention in a Temporary Quarantine Hotel in a Southern Province of Thailand: Tanika Lanwong - Tinkaew, Phenpitcha; Lanwong, Tanika; Thongnueanual, Suchathinee; Phoomchaiya, Sirimas; Christraksa, Wilawan (Princess of Naradhiwas University Journal, 2024)
This evaluation research aimed to evaluate readiness preparation and COVID-19 pandemic prevention behavior among hotel employees in a temporary quarantine hotel following readiness preparation training for the first COVID-19 pandemic prevention by using the system theory and Ralph Tyler's basic principles of evaluation. Hotel staff employed in three temporary quarantine hotels who underwent readiness preparedness training for COVID-19 pandemic prevention were chosen using purposive sampling method. 26 hotel employees completed questionnaires, while twelve hotel employees were given in-depth interview. Four instruments were used to collect data: 1) general personal information; 2) readiness evaluation; 3) assessment of infection prevention behavior; and 4) guidelines for in-depth interviews. The content validity of all instruments was validated by three experts was equal to 1. The alpha Cronbach coefficient was used to test the reliability of the readiness evaluation and the infection prevention behavior assessment, with results of 0.93 and 0.96, respectively. The data were analyzed using the mean, percentage, and standard deviation of each item and the total item. Qualitative data was analyzed using content analysis. The results of this study found that the readiness of hotel employees in COVID-19 infection prevention was at a high level (M = 4.00, S.D. = 0.58), and COVID-19 infection prevention behavior was at a high level (M = 4.30, S.D. = 0.79). As a result, this preparation can support hotel employees ‘readiness and strong COVID-19 infection prevention behavior.